Visual monitoring of goal-directed aiming movements - Brière, Julien; Proteau, Luc (Quarterly journal of experimental psychology (2006), 2017)
Goal-directed movements are subject to intrinsic planning and execution variability, which requires that the central nervous system closely monitor our movements to ensure endpoint accuracy. In the present study, we sought to determine how closely the visual system monitored goal-directed aiming movements. We used a cursor-jump paradigm in which a cursor was unexpectedly translated soon after movement initiation. Some of the trials included a second cursor jump, and the cursor remained visible for different durations. The results indicate that seeing the cursor for only 16 ms after the second cursor jump was sufficient to influence the movement endpoint, which suggests that the visual system continuously monitored goal-directed movements. The results also suggest that the perceived position/trajectory of the effector was likely to have been averaged over a period of approximately 70 ms.